STUDENTS' POSITIONING AND EMOTIONS IN LEARNING GEOMETRIC DEFINITION - Wajeeh Daher (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2020)
The purpose of the present paper is to study the positions and emotions of grade 7 students who work with technology to learn geometry. This consideration of students’ emotions is socially based, which makes it necessary to use a socially-based theoretical framework in order to study them. One such theory is the discursive analysis framework suggested by Evans, Morgan, and Tsatsarony, which is utilized in the present paper to analyze the positioning and emotions of fifteen groups of grade seven students who utilized technology to investigate the circle topic. The findings show that the group leaders took their positions through knowledge, action, initiation, persistence and meta-processes, while the followers of directions took their positions by accepting the group leader's requests. What most distinguished the collaborator was the communication with the other members of the group. Furthermore, the insiders used pronouns that indicated their inclusion. The results show that technology nurtured students' positive emotions as a result of nurturing their positioning throughout the investigation of the circle topic.